Case Report: Cardiac Tamponade in Association With Cytokine Release Syndrome Following CAR-T Cell Therapy - Moriyama, Shohei; Fukata, Mitsuhiro; Yokoyama, Taku; Ueno, Shohei; Nunomura, Takuya; Mori, Yasuo; Kato, Koji; Miyamoto, Toshihiro; Akashi, Koichi (Frontiers in Cardiovascular Medicine, 2022)
Chimeric antigen receptor T (CAR-T) cell therapy has been shown to have substantial efficacy against refractory hematopoietic malignancies. However, it frequently causes cytokine release syndrome (CRS) as a treatment-specific adverse event. Although cardiovascular events associated with CAR-T cell therapy have been increasingly reported recently, pericardial disease is a rare complication and its clinical course is not well characterized. Here, we report a case of acute pericardial effusion with cardiac tamponade after CAR-T cell therapy. CASE SUMMARY: A 59-year-old man with refractory diffuse large B-cell lymphoma underwent CAR-T cell therapy. Grade 2 CRS was observed on day 0; it progressed to grade 4 on day 7 and was accompanied by a fever over 39℃, hypoxia requiring intubation, hypotension requiring the use of a vasopressor agent, and supraventricular tachycardia. Although cardiac function was preserved, marked pericardial effusion with the collapse of the right heart was detected on echocardiography. Since pericardiocentesis was considered to have a high complication risk due to severe myelosuppression, medications for CRS were prioritized. Tocilizumab, an interleukin-6 inhibitor, and high-dose methylprednisolone (1 g/day for 3 days) were administered for the management of severe CRS. On day 8, the pericardial effusion decreased, and the hemodynamic status markedly stabilized. CRS did not exacerbate after the steroid dose was reduced. Further, lymphoma size reduced after the induction of CAR-T cell therapy, and tumor regrowth was not noted at 3 months after CAR-T cell infusion. CONCLUSION: Interleukin-6 pathway inhibitors and corticosteroid therapy should be considered in the context of CRS for significant pericardial effusion after CAR-T cell therapy in the acute phase.